463 Understanding the role of nurses in deprescribing medicines for older people: A systematic review. (13th April 2023) - Hart, L; Berrou, I
Abstract: Introduction: It is predicted that by 2035, two-thirds of people aged over 65 in the UK will be living with multiple health conditions requiring a life-long intake of multiple medicines (1). Recent reports suggest that over 8.4 million people take 5+ medicines, and 3.8 million take 8+ medicines (2). Polypharmacy, the concurrent intake of multiple medicines (5+) by one person is not problematic if the multiple medicines are prescribed appropriately to achieve clear therapeutic objectives and minimise harm. However, problematic polypharmacy arises if the risks of medicines exceed their benefits due to drug interactions and adverse drug reactions. Deprescribing is a personalised medicine optimisation intervention to ensure the safe and effective withdrawal of medicines that are no longer appropriate, beneficial or wanted. Several studies explored the role of pharmacists and doctors in deprescribing medicines for older people, and the benefits to patients and the health care system. However, literature on the nurses' role in this process remains scarce, despite their frequent contact with older people. Aim: To review the relevant studies to identify the role nurses play in deprescribing for older people. Methods: This is a systematic review of qualitative and quantitative studies, published in Embase, CINHAL, Google Scholar, British Nursing Database and PubMed, between 2012 and 2022. A manual search of reference lists of included studies was also conducted. We used key words such as nurse, nurse prescriber, deprescribing and medication optimisation to search for studies reporting on the role of nurses in deprescribing medicines for older people >65 years of age, in all healthcare settings. The quality of studies was appraised using the Critical Appraisal Skills Programme (CASP) tool. Thematic analysis was used to identify recurrent themes or concepts from the included studies, and these were then synthesised to answer the research question. Results: Twelve studies met the inclusion criteria, 11 of which were of qualitative design. All of the included studies were of moderate to high quality. Five critical roles of nurses in deprescribing were identified including: (i) Assessors; (ii) Co-ordinators; (iii) Facilitators, (iv) Communicators; and (v) Educators. Deprescribing requires multidisciplinary collaboration with clear communication between healthcare providers, and nurses are key players through their management of patients and physically effecting prescribing and deprescribing. They also have a role in assessing patients for deprescribing opportunity, coordinating multidisciplinary healthcare professional support, communicating with patients, relatives and other healthcare professionals, and educating nurses and other healthcare professionals on the importance of deprescribing as a discipline. Despite this, deprescribing is not yet integrated into nurse medication administration, prescribing, and initial or continued professional development. Conclusion: Evidence on the role of nurses in deprescribing for the older people is limited. However, the studies included in this systematic review highlight the crucial role nurses play in all stages of the process. Further exploration is required to understand the role of the nurse in deprescribing and how their initial and continued professional development can be optimised to support it. References: 1. Kingston A, Robinson L, Booth H, Knapp M, Jagger C. Projections of multi-morbidity in the older population in England to 2035: estimates from the Population Ageing and Care Simulation (PACSim) model. Age and Ageing. 2018;47(3):374-380. 2. Department of Health & Social Care. Good for you, good for us, good for everybody [Online]. 2021. Available from: https://assets.publishing.service.gov.uk/government/uploads/system/uploads/attachment_data/file/1019475/good-for-you-good-for-us-good-for-everybody.pdf (accessed 4/4/2022)